Multi-scale response characteristics of overlying soil-tunnel system under reverse fault dislocation - Haitao YU; Tingting LI; Xiao YAN (Shuiwen dizhi gongcheng dizhi, 2025)
The propagation and rupture process of bedrock fault dislocation in the overlying soil layer is controlled by many factors, which makes the response mechanism of the tunnel structure crossing the overlying soil under fault dislocation unclear. To solve this problem, a three-dimensional discrete-continuous coupling model is established, in which the discrete element is used to simulate the microscopic characteristics of the soil particles and deformation mode of the overburden layer, the finite difference method is used to calculate the macroscopic mechanical response of the tunnel structure, and the interface coupling is used to realize the interactive transfer between the above two methods. Based on the multi-scale model, the rupture propagation process of bedrock fault dislocation in the overlying soil layer, as well as the deformation response of the tunnel structure in the overlying soil are investigated. The effects of the fault dip and the depth of tunnel on the tunnel failure mode are also investigated. Results show that the bedrock fault dislocation propagates in the form of shear zone in the overburden, and the existence of tunnel structure will increase the deformation area of the soil. The deformation mode is the anti-symmetric distribution of lining stress in the upper and lower disks of the bending area caused by longitudinal bending of the tunnel, and the structural failure of the tunnel structure occurs firstly in the upper disk section, which shows the significant effect of the upper disk. Suffering the same bedrock dislocation, the tunnel structural is more likely to be damaged with a smaller fault dip. In addition, under a higher depth of tunnel, the deformation zone of the surrounding soil will be concentrated, resulting in the instability of the tunnel. The study can provide a scientific basis for the seismic design of tunnel structures in the overlying soil under the action of bedrock fault dislocation.